Letter from Julia Morgan to Cousin Lucy and Cousin Pierre Le Brun, August 15, 1897 - Julia Morgan::::::author::: (1897)
On August 15th, 1897, Julia Morgan wrote to her cousins Lucy and Pierre Le Burn from Luzarches, France. She tells of the Grand Prix de Rome. She updates her cousins on her family and her friends in Paris. She notes that the next examination date for the L'?cole des Beaux Arts is October 15th. She describes the petit chateau she is staying in Bellefontaine with a frenchwoman and the village. She closes the letter by thanking them for the "Architect" and with pleasantries.